Tata Kelola Akuntansi Masa Pemerintahan Raja Airlangga (Accounting Governance For The Government Of King Airlangga) - Lutfillah, Novrida Qudsi (Akutansi Bisnis & Manajemen ( ABM ), 2022)
This study aims to determine the practice of accounting governance during the reign of King Airlangga in 1019-1043. Historiography is used in this study by accumulating all data into a series of historical exposures of the Airlangga government. The results show that accounting governance is manifested as a charismatic form of King Airlangga's power in regulating the leadership system by taking notes on inscriptions. Godliness is used as a basis in governance to achieve the welfare of the people. This can be seen from the determination of sima, construction of agricultural facilities and expansion of international trade.